Alleviation of the pain of heel prick in preterm infants. Issue 3 (May 1994) - McIntosh, N; van Veen, L; Brameyer, H
Abstract : The hypothesis that the variability of physiological parameters may indicate pain or stress in the neonate was examined. Four parameters (heart rate, respiratory rate, transcutaneous oxygen tension, and carbon dioxide tension) were examined over a 2 minute epoch in response to a heel prick in an attempt to measure stress/pain in 35 preterm newborn infants (26-34 weeks' gestation) half of whom were receiving intensive care. The change in absolute values of these parameters did not discriminate a dummy procedure without prick from the actual procedure containing the prick (paired t test), but the variability of the parameters during an epoch showed significant discrimination. Three procedures were evaluated to reduce this distress using unpaired t test. The use of local anaesthetic cream was not successful. The components of the mixture cause vasoconstriction that would reduce blood flow to the heel and lead to more squeezing which is likely to be painful in the presence of tissue damage. A nurse comforting the infant with tactile and vocal stimulation was slightly helpful but the use of a spring loaded lance was most successful in reducing the distress. The use of spring loaded lances may be more humane for heel pricks.